The Role of Correction Center (Bapas) Accepting Children In Conflict With The Law (Study on Class II Penitentiary Office in Bojonegoro) - PURWANTO, GUNAWAN HADI (Jurnal Independent, 2022)
ABSTRAKChildren are an integral part of human survival and the survival of a nation and state.In the Indonesian Constitution, children have a strategic role which is expressly stated that thestate guarantees the right of every child to save life, grow and develop as well as protectionfrom violence and violence. Therefore, the best interests for children should be internalized asthe best interests for sustaining human life. Children in conflict with the law, hereinafterreferred to as children, are children who are 12 (twelve) years old but not yet 18 (eighteen)years old who are suspected of committing a crime. Of course the handling of children who areperpetrators of criminal acts must receive special treatment and handling from relatedinstitutions, in this case the Correctional Institutions (BAPAS) as stipulated in Law Number 11of 2012 concerning the Juvenile Criminal Justice System and Government Regulation of theRepublic of Indonesia Number 65 of 2015 concerning Guidelines for the Implementation ofDiversion and Handling of Children Who Are Not Yet 12 (Twelve) Years Old In the case ofchildren who are not yet 12 (twelve) years old, along with technical regulations from therelevant ministries.Keywords: Role, Correctional Center, Children in Legal Conflict